New Technologies for the Treatment of Coronary and Structural Heart Diseases - Polimeni, Alberto (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
There has been significant progress in the field of interventional cardiology, from the development of newer devices to newer applications of technology, resulting in improved cardiovascular outcomes. The goal of this Special Issue is to update practicing clinicians and provide a comprehensive collection of original articles, reviews, and editorials. To this end, we invited state-of-the-art reviews, including reviews of new technology and therapeutics, as well as original research in this area to be considered for inclusion in this issue. Examples include the history and evolution of interventional techniques, reviews of specific devices and technologies for coronary artery disease (i.e., stent technology, atherectomy devices, coronary physiology, intracoronary imaging, and robotics), structural heart diseases (i.e., ASD: atrial septal defect; LAAC: left atrial appendage closure; MC: MitraClip; PFO: patent foramen ovale; TAVI: transcatheter aortic valve implantation), advances in the management of challenging coronary anatomy, new biomarkers of cardiovascular disease (noncoding RNAs, etc.), and interventional techniques in the management of heart failure, peripheral arterial diseases, and pulmonary embolism. This Special Issue presents the most recent advances in the field of coronary and structural heart diseases as well as their implications for future patient care.